Protective effect of Xingnaojing injection on ferroptosis after cerebral ischemia injury in MCAO rats and SH-SY5Y cells. (30th January 2023) - Liu, Haoqi; An, Na; Wang, Liqin; Li, Yuanyuan; Song, Ke; Sun, Yikun; Gao, Yonghong
Abstract : Ethnopharmacological relevance: Xingnaojing（XNJ）injection is a traditional Chinese medicine injection with neuroprotective effect, which has been widely used in the treatment of stroke for many years. Aim of the study: This study aimed to explore the potential mechanism of XNJ in cerebral ischemia mediated by ferroptosis using proteomics and in vivo and in vitro experiments. Materials and methods: After the rat model of middle cerebral artery occlusion (MCAO) was successfully established, they were randomly divided into model, XNJ, and deferoxamine (DFO) group. Triphenyl tetrazolium chloride (TTC) staining, Hematoxylin and eosin (H&E), and Nissl staining were used to observe the infarct area, pathological changes and the degree of neuronal apoptosis of rat brain. Proteins extracted from rat brain tissues were analyzed by quantitative proteomics using tandem mass tags (TMT). Western blotting and immunohistochemical assessment were used to measure the expression of ferroptosis-related proteins. In vitro, the SH-SY5Y cells were subjected to hypoxia (37°C/5% CO2 /1% O2 ) for 24 h to observe the survival rate, and detect the reactive oxygen species (ROS) content and ferroptosis-related proteins. Results: In TTC and H&E experiments, we found that XNJ drug treatment reduced the infarct volume and brain tissue damage in MCAO rats. Nissl staining also showed that compared with MCAO group rats, the Nissl bodies of brain tissue after XNJ drug intervention were clear with a 3.54-fold increased times, suggesting that XNJ improved cerebral infraction, and neurological deficits in MCAO rats. Proteomics identified 101 intersected differentially expressed proteins (DEPs). According to the bioinformatics analysis, these DEPs were closely related to ferroptosis. Further research indicated that MCAO-induced cerebral ischemia was alleviated by upregulating recombinant glutathione peroxidase 4 (GPX4), ferroportin (FPN) expression, Heme oxygenase-1 (HO-1) expression, and downregulating cyclooxygenase-2 (COX-2), transferring receptor (TFR) and divalent metal transporter-1 (DMT1) expression after XNJ treatment. In addition, in vitro experiment indicated that XNJ improved the survival rate of hypoxia-damaged SH-SY5Y cells. XNJ increased the level of GPX4 and inhibited the protein expression of COX-2 and TFR after cell hypoxia. Moreover, different concentrations of XNJ (0.25%, 0.5%, 1%) reduced the ROS content of hypoxic cells, suggesting that XNJ could inhibit hypoxia-induced cell damage by regulating the expression of ferroptosis-related proteins and decreasing the production of ROS. Conclusions: XNJ could promote the recovery of neurological function in MCAO rats and hypoxia SH-SY5Y cells by regulating ferroptosis. Graphical abstract: Image 1 Highlights: Xingnaojing (XNJ) could protect brain injury by inhibiting ferroptosis and oxidative stress after cerebral ischemia. XNJ decreased the expression levels of COX2, TFR and increased the levels of GPX4, HO-1 in MCAO rats. In Hypoxic SH-SY5Y cells, XNJ decreased the expression of COX2, TFR, ROS and increased the levels of GPX4 and HO-1.